A monitoring network for the detection of invasive ambrosia and bark beetles in the Czech Republic: principles and proposed design - Fiala, Tomáš; Holuša, Jaroslav (Frontiers in Forests and Global Change, 2023)
Invasive bark beetles pose a threat to native biodiversity and to functional ecosystems and the economic productivity of forests, parks, and orchards. In the Czech Republic, there are six species of invasive ambrosia and bark beetles with a stable natural population, and it can be assumed that other invasive species that will be found. In the Czech Republic, there are no guidelines or methods for the early detection of invasive ambrosia and bark beetles. We propose monitoring at a total of 24 locations considering the following: (i) monitoring approaches used in other countries; (ii) identified entrance gates of invasive ambrosia and bark beetles found in the Czech Republic; (iii) presumed invasive species that occur in surrounding countries and are expanding their range; (iv) substances attractive to all the above mentioned species; (v) commonly available traps; and (vi) minimization of operating costs. Most of the chosen locations are located on the state borders and in river valleys, which are probably the entrance gates to the Czech Republic for invasive ambrosia and bark beetles. In addition, two large timber warehouses where international trade takes place, all international airports and three botanical gardens with tropical greenhouses were selected. Three Theysohn or Ecotrap impact traps should be installed every year at all locations. Traps should be baited with ethanol and exposed from mid-April to the end of July and should be checked every 2 weeks.